Fragile X syndrome - insight into what we know and prospects - Strzoda, Adam; Kamińska, Magdalena; Strzoda, Anna; Strzoda, Agata; Sowiński, Wojciech; Zdybel, Michał; Juda, Agata; Rojek, Kornelia (Journal of Education, Health and Sport, 2023)
Fragile X syndrome is a dominantly inherited genetic disease and is a consequence of the FMR1 gene mutation located on the X chromosome. The number of patients affected by this disease with full mutation is estimated at 1 in 4000 men and 1 in 8000 women, however, the number of carriers with premutation is far greater. Depending on the mutation of the FMR1 gene and levels of its products FMRP a variety of symptoms can be observed including- intellectual disability, mental retardation, lowered behavioral adaptation, autism, and dysmorphic features such as a long face with a broad forehead and prominent ears. The treatment is mostly symptomatic- managing comorbidities and an emphasis on psychological therapy. The objective of this paper is to sum up the most up-to-date knowledge regarding the pathogenesis, treatment- current and clinically tested, and novelties in the Fragile X syndrome